Reaching the mountaintop of the academy : personal narratives, advice, and strategies from Black distinguished and endowed professors - Thompson, Gail L., 1957-; Bonner, Fred A.; Lewis, Chance W. 1972- (Contemporary perspectives on access, equity, and achievement., 2016)
Since the U.S. Civil Rights era, the racial composition of higher education has changed dramatically, resulting in an increase in the number of African American students and African American faculty in predominantly white institutions (PWI). Nevertheless, the number of African American endowed or distinguished professors remains small.Because it is difficult for African American faculty to attain these prized positions, those who have done so possess invaluable knowledge that may be beneficial to others. Reaching the Mountaintop of the Academy: Personal Narratives, Advice and Strategies from Black Distinguished and Endowed Professors, fills an important niche in the canon of higher education literature. In the autobiographical chapters that follow, numerous distinguished and endowed professors (1) describe their personal journey to the distinguished or endowed professorship; (2) explain important life lessons that they learned during their journey; (3) describe their current professional goals; and (4) offer suggestions and recommendations for graduate students, untenured faculty, tenured faculty, and college/university administrators. At a time when many predominantly white higher education institutions continue to have difficulty attracting and retaining African American faculty, and African American faculty continue to struggle for full inclusion in the academy, this book is timely and needed.